Reading and Learning to Read - Vacca, Jo Anne L., Vacca, Richard T. and Gove, Mary K.; Published by Robert Frederick Ltd. (New York, NY HarperCollins, 1991)
With its balanced approach to reading instruction, Reading and Learning to Read, 4/e, remains a comprehensive, active learning tool that encourages students to teach reading in ways that are both meaningful and reflective. This renowned author team explores how beliefs about reading and writing influence the ways in which teachers work with children in classrooms and provides practical, effective strategies for helping all children learn to read.
Include Colored Illustrations, Appendix, Biliography and Index.
Keywords: Reading (Elementary)